Semantic-Cognitive Analysis of the Concept PANDEMIC (Based on English Media Texts) - E. V. Korovina; N. V. Stepanova (Дискурс, 2022)
Introduction. The purpose of this study is to conduct a consistent semantic-cognitive analysis of the PANDEMIC concept based on the material of the pandemic period current media texts. The present study examines the objectification of the PANDEMIC concept in English-language media texts. The relevance of the linguo-cognitive representation study of the concepts of the pandemic crisis discourse is beyond doubt, since the events and phenomena of the crisis period are directly reflected in these cognitive units, with the help of which certain images are constructed in the social consciousness and, thus, public opinion is formed on key socially relevant issues.Methodology and sources. While constructing the nominative field of the PANDEMIC concept, methods of discursive and conceptual analysis were used, including recourse to the analysis of dictionary definitions and synonymic series, as well as an interpretive analysis of the context based on media texts. The material of the study was the media texts of the news resources selected from March 2020 to January 2022.Results and discussion. As a result of the study of the PANDEMIC concept, numerous cognitive features were identified. At the core of the PANDEMIC concept there are two cognitive features: harm to health and spread over vast areas. The composition of the near periphery of the PANDEMIC concept included the following cognitive features: encouraging and forcing to vaccinate; using of personal protective equipment; social isolation or quarantine; fighting against the virus. The far periphery of the PANDEMIC concept consists of the following cognitive features: fear and anxiety caused by the virus; the negative impact of the pandemic on the business and economic development of countries; the positive impact of the pandemic on the business and economic development of countries; change in normal routine.Conclusion. The semantic-cognitive analysis allows for the transition from the semantic component of language units to the content of the concept. The stylistic and phraseological units that make up the figurative component and the interpretive field of the concept provide an opportunity to expand the boundaries of the cognitive unit and construct the image of pandemic even more thoroughly.